Examining service shortfalls: A case study of Chinese group package tours to Australia. (October 2018) - Chen, Hanyu; Weiler, Betty; Young, Martin
Chinese inbound tourism constitutes Australia's fastest growing and largest international tourist market. Currently, most of this travel is conducted via group package tours (GPTs). While there is anecdotal evidence of dissatisfaction with some aspects of Chinese tourists' service experience such as commission-based shopping, little empirical evidence is available about the salient dimensions of service quality or their respective performance. The aim of this study is to identify the core service components offered by Chinese GPTs and to examine any service shortfalls. Findings from a survey of 520 tourists revealed three dimensions of Chinese package tour service: attractions, tour leader and food and accommodation . The study identified significant gaps between expectation and performance across all dimensions. Theoretical and service quality implications for researchers, tour operators and policymakers are presented and discussed.